2006
DOI: 10.1002/ijc.21775
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PD‐L1 (B7‐H1) augments human tumor‐specific T cell responses in vitro

Abstract: Human tumors frequently escape immune destruction, despite the presence of cyototoxic T cells (CTL) recognizing tumor-associated antigens (TAA). We have previously shown that programmed death ligand-1 (PD-L1), a recently identified ligand of the B7 superfamily, is expressed on murine tumors and can inhibit antitumor immune responses. To evaluate the clinical relevance of our animal model findings, we examined human tumors and tumorspecific T cells. We found PD-L1 to be constitutively expressed on human renal c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
205
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(219 citation statements)
references
References 78 publications
11
205
0
3
Order By: Relevance
“…Many groups of investigators have reported that blockade of the PD-1/PD-L1 interaction promotes tumor immunity. [35][36][37] Conversely, there remains a problem regarding PD-1/PD-L1 blockade because of the possible expansion of poorly immunogenic cells. 38 Further studies may be required to clarify the therapeutic effect of PD-1/PD-L1 blockade in malignant melanoma models and clinical trials.…”
Section: Pd-l1 Expression In Malignant Melanomamentioning
confidence: 99%
“…Many groups of investigators have reported that blockade of the PD-1/PD-L1 interaction promotes tumor immunity. [35][36][37] Conversely, there remains a problem regarding PD-1/PD-L1 blockade because of the possible expansion of poorly immunogenic cells. 38 Further studies may be required to clarify the therapeutic effect of PD-1/PD-L1 blockade in malignant melanoma models and clinical trials.…”
Section: Pd-l1 Expression In Malignant Melanomamentioning
confidence: 99%
“…T cells become progressively more nonresponsive as they express additional inhibitory receptors (9). Tumor-infiltrating T cells may also be functionally inert, due in part to the expression of PD-1 along with other inhibitory receptors (10,11). In multiple syngeneic mouse tumor models, blockade of PD-1 or its ligands promotes antitumor activity (12)(13)(14); anti-PD-1 activity in vivo can be enhanced by combination with antibodies to other T-cell negative regulators, such as CTLA-4 and LAG-3 (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 is expressed by many human tumors, including melanoma, lung, and kidney (10,18,19). PD-L1 engagement of PD-1 may be one mechanism whereby tumors evade immunosurveillance by directly limiting effector T-cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies that block the interaction between PD-L1 and its cognate receptors can relieve PD-L1-dependent immunosuppressive effects in vitro, enhancing the cytotoxic activity of antitumor T cells (19). Based in part on these observations, anti-PD-L1 antibodies could be used therapeutically to enhance antitumor immune responses in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%